2003
DOI: 10.1073/pnas.1032925100
|View full text |Cite
|
Sign up to set email alerts
|

The lethal effects of transplantation ofSocs1-/-bone marrow cells into irradiated adult syngeneic recipients

Abstract: Injection of neonatal bone marrow cells from mice lacking the gene encoding suppressor of cytokine signaling 1 (SOCS1) into irradiated syngeneic 129͞Sv or C57BL͞6 mice led to a decreased survival, more rapidly occurring in 129͞Sv than in C57BL͞6 mice. Moribund mice did not exhibit the acute or chronic diseases developed by Socs1 ؊/؊ mice but developed a pathology characteristic of graft-versus-host disease with typical chronic inflammatory lesions in the liver, skin, lungs, and gut. The results indicate that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…SOCS1 functions as a negative regulator of signaling by various cytokines, such as IFN-γ, IL-2, IL-6, IL-7, IL-12, and IL-15, by inhibiting the Janus kinases (JAKs)/STAT in T cells and other immune cells (5, 6). Metcalf D. et al (7) reported that adoptive transfer of bone marrow (BM) cells of neonatal SOCS1-deficient ( −/− ) mice into irradiated syngeneic mice caused a pathology characteristic of graft-versus-host disease with chronic inflammatory lesions in multiple organs of the recipients, in agreement with earlier findings (6). Hanada T. et al further demonstrated that SOCS1 −/− transgenic mice in which SOCS1 expression had been restored in T and B cells on a SOCS1 −/− background developed only mild autoimmune diseases and that SOCS1 −/− DCs were hyper-responsive to LPS and IFN-γ and triggered allogeneic T cell expansion (8).…”
Section: Introductionsupporting
confidence: 77%
“…SOCS1 functions as a negative regulator of signaling by various cytokines, such as IFN-γ, IL-2, IL-6, IL-7, IL-12, and IL-15, by inhibiting the Janus kinases (JAKs)/STAT in T cells and other immune cells (5, 6). Metcalf D. et al (7) reported that adoptive transfer of bone marrow (BM) cells of neonatal SOCS1-deficient ( −/− ) mice into irradiated syngeneic mice caused a pathology characteristic of graft-versus-host disease with chronic inflammatory lesions in multiple organs of the recipients, in agreement with earlier findings (6). Hanada T. et al further demonstrated that SOCS1 −/− transgenic mice in which SOCS1 expression had been restored in T and B cells on a SOCS1 −/− background developed only mild autoimmune diseases and that SOCS1 −/− DCs were hyper-responsive to LPS and IFN-γ and triggered allogeneic T cell expansion (8).…”
Section: Introductionsupporting
confidence: 77%
“…However, unlike GMRβc, SOCS-1 did not negatively regulate the expression level of EPOR. This is consistent with previous findings showing that JAK2-mediated degradation of EPOR is dependent on another E3 ligase containing the F-box protein β-TrCP [21],[22] and that progenitor cells from SOCS-1 −/− mice are hypersensitive towards GM-CSF but not to other cytokines such as M-CSF or G-CSF [23], [24]. It is at present unclear why the recruitment of SOCS-1 to certain activated cytokine receptors leads to the degradation of only JAK2 via SOCS-1 while the receptor itself is targeted by another E3 ubiquitin ligase, such as in the case for the EPOR, whereas SOCS-1 recruitment to activated GMR results in the degradation of both JAK2 and GMRβc via SOCS-1.…”
Section: Discussionsupporting
confidence: 93%
“…Despite the prominent role of SOCS-1 for IFN-␥ signaling it has also been shown that hematopoetic progenitor cells of SOCS-1 knockout mice have an increased sensitivity to GM-CSF but not to M-CSF. 18,19 It is noteworthy that the CSF-1 receptor belongs to the receptor-tyrosine kinase family, which in general is not a reported target of SOCS proteins. This could explain why TLR stimulation results in inhibition of GM-CSFmediated DC formation but has no effects on the generation of a more macrophage-like phenotype, which possibly is due to effects of intrinsic CSF as a kind of default pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, SOCS-1 knockout mice, in spite of a lethal phenotype due to hypersensitivity 16,17 toward IFN-␥, also exhibit hyperresponsiveness to GM-CSF. 18,19 We and others have shown that TLR stimulation in innate immune cells results in the induction of various SOCS members, thereby regulating the responsiveness to cytokine stimulation as shown in detail for IFN-␥. [20][21][22] We now tested the hypothesis that by means of induction of SOCS proteins, TLR-dependent signals influence differentiation of DCs from precursor cells.…”
Section: Introductionmentioning
confidence: 98%